2016
DOI: 10.21873/anticanres.11085
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole, an Antipsychotic and Partial Dopamine Agonist, Inhibits Cancer Stem Cells and Reverses Chemoresistance

Abstract: Repurposing aripiprazole as an anticancer stem cell drug may merit further consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 18 publications
3
43
0
Order By: Relevance
“…While it is, thus, suggested that olanzapine may enhance the growth inhibitory effect of various chemotherapeutic agents through the promotion of cell death due to decreased survivin expression, it still remains to be shown in the present study how olanzapine reduces survivin expression. Given that aripiprazole, another atypical antipsychotic drug, similarly reduces the expression of survivin in cancer cells as we demonstrated earlier (11), target receptors shared by olanzapine and aripiprazole may be involved in the regulation of survivin expression. In this regard, it might be interesting to note that serum survivin levels were found to be elevated in prolactinoma patients treated with dopamine D 2 receptor agonists (bromocriptine or cabergoline) in a recent study (35).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…While it is, thus, suggested that olanzapine may enhance the growth inhibitory effect of various chemotherapeutic agents through the promotion of cell death due to decreased survivin expression, it still remains to be shown in the present study how olanzapine reduces survivin expression. Given that aripiprazole, another atypical antipsychotic drug, similarly reduces the expression of survivin in cancer cells as we demonstrated earlier (11), target receptors shared by olanzapine and aripiprazole may be involved in the regulation of survivin expression. In this regard, it might be interesting to note that serum survivin levels were found to be elevated in prolactinoma patients treated with dopamine D 2 receptor agonists (bromocriptine or cabergoline) in a recent study (35).…”
Section: Discussionsupporting
confidence: 69%
“…So far, we have tested the effects of olanzapine solely on CSCs. This is because we mainly used CSCs as experimental models to explore possible anticancer activities of aripiprazole in our earlier study and it, thus, remained unknown whether aripiprazole has a chemosensitizing activity in serum-cultured, non-stem cancer cells (11). We, therefore, asked next in this study whether olanzapine can inhibit survivin expression not only in CSCs but also in serum-cultured non-CSCs.…”
Section: The Effect Of Olanzapine On Survivin Expression and Chemosenmentioning
confidence: 98%
See 1 more Smart Citation
“…Briefly, the cells were cultured on collagen‐I‐coated dishes (IWAKI, Tokyo, Japan) in stem cell culture medium [DMEM/F‐12 supplemented with 1% B27 (Thermo Fisher Scientific), 20 ng·mL −1 EGF and FGF2 (Peprotech, Rocky Hill, NJ, USA), D‐(+)‐glucose (final concentration, 26.2 m m ), L‐glutamine (final concentration, 4.5 m m ), 100 units·mL −1 penicillin and 100 μg·mL −1 streptomycin]. Rat cortical NSCs were purchased from R&D Systems (Minneapolis, MN, USA) and cultured on Geltrex (Thermo Fisher Scientific)‐coated dishes in the stem cell culture medium . The stem cell culture medium was changed every 3 days, and EGF and FGF2 were added to the stem cell culture medium daily.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, cells were cultured on collagen‐I‐coated dishes (IWAKI, Tokyo, Japan) in stem cell culture medium (DMEM/F‐12 supplemented with 1% B27 [Thermo Fisher Scientific], 20 ng·mL −1 EGF and FGF2 [Peprotech, Inc., Rocky Hill, NJ, USA], d ‐(+)‐glucose [final concentration 26.2 m m ], l ‐glutamine [final concentration 4.5 m m ], 100 units·mL −1 penicillin and 100 μg·mL −1 streptomycin). Rat cortical neural stem cells (NSCs) were purchased from R&D systems (Minneapolis, MN, USA) and cultured on Geltrex (Thermo Fisher Scientific)‐coated dishes in the stem cell culture medium . The stem cell culture medium was changed every 3 days, and EGF and FGF2 were added to the stem cell culture medium every day.…”
Section: Methodsmentioning
confidence: 99%